ANALISIS IUS CONSTITUENDUM PENEGAKAN HUKUMKEJAHATAN GENOSIDA PADA KASUS ROHINGYA:REFLEKSI ATAS KASUS HOLOCAUST - Syafik Fadel Salim, (2023)
Genocide as an international crime against humanity is a reaction to the Holocaust incident which was a massacre with the aim of exterminating ethnic minorities. Years after the Holocaust, genocide has spread internationally, and there is no law enforcement that can stop and prevent genocide optimally. Rohingya is another genocide crime case that occurred in Myanmar which until now has not been resolved and is evidence of the inadequate legal instruments available in dealing with genocide crimes. This study aims to find out what law enforcement aspires to (ius constituendum) and which can uphold cases of genocide crimes to the fullest and also the implementation of efforts to resolve genocide in Rohingya referring to the settlement in the Holocaust case. This legal research is normative juridical which is carried out using the research method of library research and takes the source of legal materials used with primary and secondary legal materials. The results of this study indicate that in an effort to produce ius constituendum from law enforcement for the crime of genocide, it is necessary to change or reconstruct several aspects of existing legal instruments and international organizational principles so that they can support optimal enforcement of the crime of genocide. In addition, assistance from the international community and international organizations is needed to directly take legal steps to stop the Rohingya genocide in Myanmar. Keywords : Genocide, Ius Constituendum, Law Enforcement, Holocaust, Rohingya